POLA PERDAGANGAN INDONESIA-TIONGKOK - Manat Rahim; Heppi Millia (Universitas Negeri Padang, 2014)
Abstract: This study aimed to analyze the pattern of trade between Indonesia and China, the role of China as a market commodity exports, and as a supplier of imported commodities Indonesia. And identify commodities that include strong, stable and weak in entering the Chinese market. By using secondary data and descriptive quantitative analysis tools, this research generates; (1) The development of Indonesia's export destination is smaller than the development of China's imports from China, the trade balance deficit continues to expand, the intensity of the small trade and tends to decline. (2) The role of China in the larger Indonesian International trade, both as a market share of non-oil exports as well as suppliers of raw materials and capital goods. Even has shifted USA, EU, and Japan. (3) commodity exports has a strong position is; Nickel, coal, crabs, and plywood. While commodities are in a stable position is; Shrimp, palm oil, rubber, power tools, fruits, and copper and copper products have a stable position. Brown, Paper and paper products, as well as computers and computer parts in Chinese market. Keywords: Patterns of Trade, Indonesia, China Abstrak : Penelitian ini bertujuan untuk menganalisis pola perdagangan Indonesia-Tiongkok, peran Tiongkok sebagai pasar komoditas ekspor, dan sebagai pemasok komoditas impor Indonesia. Serta mengidentifikasi komoditas yang termasuk kuat, stabil dan lemah dalam memasuki pasar Tiongkok. Dengan menggunakan data sekunder dan alat analisis kuantitatif deskriptif, penelitian ini menghasilkan; (1) Perkembangan ekspor Indonesia tujuan Tiongkok lebih kecil dari perkembangan impor asal Tiongkok, neraca perdagangan defisit makin membesar, intensitas perdagangan kecil dari satu dan cendrung menurun.(2) Peran Tiongkok dalam perdagangan Internasional Indonesia semakin besar, baik sebagai pangsa pasar ekspor non migas maupun sebagai pemasok bahan baku dan barang modal. Bahkan telah menggeser posisi USA, Uni Eropa, dan Jepang . (3) Komoditas ekspor yang mempunyai posisi kuat adalah; Nikel, batu bara, kepiting, dan kayu lapis. Sedangkan komoditas yang berada pada posisi stabil adalah; Udang, minyak sawit, karet, alat-alat listrik, buah-buahan, dan tembaga serta produk dari tembaga mempunyai posisi stabil. Coklat, Kertas dan barang dari kertas, serta komputer beserta bagiannya di pasar Tiongkok. Kata Kunci: Pola Perdagangan, Indonesia, Tiongkok